Drugs Causing Methemoglobinemia in Children - Dias, Edwin; Mahendrappa , K. B.; Arkasali , Manjunath R. (Current Overview on Disease and Health Vol. 7, 2023)
Methemoglobinemia is a rare blood disorder characterised by an increase in the proportion of oxidised haemoglobin (Methaemoglobin). Drugs rarely causes the Methemoglobinemia in adults in comparative to Children. Dapsone is the most typical medication that causes methemoglobinemia. An 8-Year-old child presented with irritability, restlessness, breathing difficulty 1 day prior to accidental ingestion of 10 dapsone tablets. Children who have a reduction reductase deficit or atypical haemoglobin may show severe adverse effects or overdose. Accurate diagnosis and treatment necessitate a good knowledge of drug prescriptions, which is critical for children.